Detrimental Consequences of Inappropriate Coping Mechanisms in My Year of Rest and Relaxation by Ottessa Moshfegh (2018) - Maisyarah, Muthia; Alamsyah, Devy Kurnia (English Language and Literature, 2024)
This research study is about the detrimental consequences of the narrator's coping mechanisms in the novel My Year of Rest and Relaxation (2018) by Ottessa Moshfegh. This study focuses on the narrator's inappropriate usage of coping mechanisms to deal with stress and pressure in her life, resulting in detrimental consequences. The study uses the psychoanalysis drive theory by Sigmund Freud and the 8 Scales of Coping Mechanisms by Folkman et al to analyze the novel. The method used in this research is descriptive qualitative. The results of this research are divided into 2, namely the type of coping mechanism used by the narrator and the detrimental consequences that arise due to the narrator's inaccuracy in using her coping mechanism. The types of coping mechanisms used by the narrator include seeking social support, positive reappraisal, distancing, and escape-avoidance. Then, the detrimental consequences that emerge include drug dependency, emotional detachment, isolation, and lack of interest.